An in-house indirect immunofluorescence test for ensuring that the cell bank is contamination free - Keshavarz, Maryam; Shafiee, Abbass; Tariqi, Gholam Reza; Izad, Maryam; Yousefi, Ahmad; Hosseinzadeh, Morteza (Archives of Medical Laboratory Sciences, 2019)
Background: Cross-contamination between cells is a usual mistake at cell culture laboratories and cell banks worldwide. MRC5 diploid cell and Rk-13, Vero and Hela continuous cell lines are used in different stages of human viral vaccines propagation at Razi Vaccine and Serum Research Institute of Iran. However diploid and continuous cells are propagated at separated cell culture laboratory and continuous cells can contaminate MRC5 diploid cells. Therefore, a sensitive test is needed. World Health Organization recommends few molecular and cellular techniques to cell characterization. Materials and Methods: The present study was therefore designed to set up an indirect immunofluorescence (IIF) test as follows: Polyclonal anti-MRC5 cell and anti-rabbit antibodies were prepared in rabbit and goat, respectability. Anti-rabbit IgG was purified using protein G affinity chromatography, conjugated to fluorescein isothiocyanate (FITC), and then further purified to remove unbound FITC using Sephadex G 25 chromatography. Using double immunodiffusion assay, purification of homemade anti-rabbit IgG was asssayed by observation of a single arch. Results: The titer of homemade FITC conjugated goat anti rabbit IgG was measured 1/16 vs 1/8 of commercial type. Fluorescein/protein molar ratio of local made fluorescein goat anti-rabbit IgG was measured 3.44 and its protein concentration and FITC concentration were determined 1.198 mg/ml and 0.01 mg/ml, respectively. Conclusion: Moreover, homemade IIF test showed 100% intra-laboratory reproducibility. Purity of three batches of MRC5 working seed cell was verified using in- house IIF test and no contamination to continuous cell lines was found .